2001
DOI: 10.1161/01.hyp.38.2.166
|View full text |Cite
|
Sign up to set email alerts
|

Iron Supplementation Inhibits Cough Associated With ACE Inhibitors

Abstract: Abstract-Dry cough is the most common limiting factor of ACE inhibitor (ACEI) use. Generation of NO, a proinflammatory substance on bronchial epithelial cells, is increased by ACEI. Using a randomized, double-blind, placebo-controlled trial, we tested the hypothesis that supplementing iron, an inhibitor of NO synthase, may reduce the cough associated with ACEI use. The subjects were 19 patients who had developed ACEI-induced cough. After a 2-week observation period, they were randomized to a daily morning dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…As observed in an earlier study, 11 iron supplementation did not result in any significant change in mean haemoglobin concentration and haematocrit readings. There were no significant changes in blood urea, serum creatinine, serum sodium and potassium concentrations.…”
supporting
confidence: 84%
“…As observed in an earlier study, 11 iron supplementation did not result in any significant change in mean haemoglobin concentration and haematocrit readings. There were no significant changes in blood urea, serum creatinine, serum sodium and potassium concentrations.…”
supporting
confidence: 84%
“…148 -150 One small study of Asian women has shown improvement or relief of cough with iron supplementation. 151 The mechanism for the increased incidence of cough is not elucidated although 1 report of Asian patients with cough that included mostly diabetic women, found an association with an ACE genetic polymorphism. 152…”
Section: Ace Inhibitorsmentioning
confidence: 99%
“…Ferrous sulphate has also been shown to reduce ACEI‐induced cough, presumably through inhibition of nitric oxide synthesis 16 . However, while ferrous sulphate therapy had only reduced the severity of ACEI‐induced cough, noscapine could eliminate the cough altogether in the vast majority of patients.…”
Section: Discussionmentioning
confidence: 99%